2008
DOI: 10.1002/pon.1449
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and spousal communication in couples coping with prostate cancer

Abstract: Objective To characterize the sexual function of both prostate cancer patients and their partners, and to examine whether associations between sexual dysfunction and psychosocial adjustment vary depending on spousal communication patterns. Methods In this cross-sectional study, 116 prostate cancer patients and their partners completed psychosocial questionnaires. Results Patients and partners reported high rates of sexual dysfunction. Within couples, patients’ and their partners’ sexual function was modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 50 publications
10
172
2
4
Order By: Relevance
“…Similar to other studies, Badr and Taylor [29] reported that within couples, patients' and their partners' sexual function and satisfaction were very similar.…”
Section: Hrqol and Survivalsupporting
confidence: 75%
“…Similar to other studies, Badr and Taylor [29] reported that within couples, patients' and their partners' sexual function and satisfaction were very similar.…”
Section: Hrqol and Survivalsupporting
confidence: 75%
“…Studies that have included partners of men with prostate cancer have described their experiences in terms of decreased intimacy, emotional burden similar to that of caregivers, and a change of role. Women reported that they were no longer the lovers in the relationship, and romance was replaced by the resultant stress from the sexual issues (Badr & Carmack Taylor, 2009;Giarelli et al, 2003). Additionally, resultant psychological and physical distress were reported to be major burdens on intimate relationships Couples with prostate cancer reported stressful relationships and distress that were affected by avoidant coping behaviors (Lavery & Clarke, 1999;Wootten et al, 2007).…”
Section: Relationship With Partnermentioning
confidence: 99%
“…For men with prostate cancer, studies have documented that sexual dysfunction resulting from treatment led to emotional distress and distancing between couples . Sexual functioning was found to be related to relationship satisfaction; therefore, men with prostate cancer with resultant sexual dysfunction reported decreased satisfaction with their intimate relationships (Badr & Carmack Taylor, 2009). The contribution of men's perceptions of their relationship dynamics on their QOL is not well understood.…”
Section: Environmental Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations